PENGUKURAN KINERJA PADA PERUSAHAAN FURNITURE DENGAN MENGGUNAKAN METODE PERFORMANCE PRISM DAN ANALYTICAL HIERARCHY PROCESS - Widiyawati, Sri; Soeparman, Sudjito; Soenoko, Rudy (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2013)
Performance measurement method, Performance Prism, was used to improve performance measurement method in this furniture company. Until now, performance measurement system in this company haven’t represented overall organizational performance since it only used performance measurement based on individual ability. Performance measurement using Performance Prism method was used because it could reflects the needs and desire of each identified stakeholder within company. This performance measurement is an integrated measurement, encompassing all company aspects (stakeholder) which related with stakeholder satisfaction and stakeholder contribution for the company. Performance measurement in this study also supported by several other methods such as weighting with Analytical Hierarchy Process (AHP) to determine priority scale of each KPI, Scoring System using Objectives Matrix (OMAX) and Traffic Light System to determine total index value of company in corporation level and category of those indices. Results of performance measurement in this company using Performance Prism indicated 79 KPI’s consist of 17 KPIs on Investor perspective, 16 KPI’s on Customer perspective, 16 KPI’s on Employee perspective, 15 KPI’s on Supplier perspective and 15 KPI’s on Regulator perspective. Based on performance measurement calculation using Objective Matrix and Traffic Light System, it obtained total index value 5,8364. This showed that performance of this furniture company still yet to reach desirable performance thus it would need some improvement in this matter.